Facility Layout Redesign of Goat Leather Kompang SME in Dumai Using Systemic Layout Planning dan Graph Method - Reza lesmana; Fitra Fitra; Wahyu Prayogi; Marzuki Marzuki (JTI: Jurnal Teknik Industri, 2025)
The traditional instrument manufacturer IKM Kompang Kulit Kambing Medan Kampai experienced major problems with inefficient facility layout. This resulted in losses for the company due to high material handling costs, long production times, and decreased productivity. Systemic Layout Planning (SLP) was the method used in this study, supported by data collection and analysis through the use of relationship diagrams and process flow diagrams. Several new layouts were created to reduce transfer distances and material management costs. This study recently focused on traditional instrument SMEs using structured industrial techniques. In addition, comparing SLP with graphical methods provides a culture-based industrial perspective. The evaluation results show that the SLP approach is the best layout method, resulting in the shortest distance of 78. Meanwhile, the Graph Method resulted in a distance of 184.8. Thus, the Kompang Kulit Kambing Medan Kampai SME must reorganize its production space to be more efficient and effective. This will increase the competitiveness of SMEs and help preserve cultural heritage through sustainable production. Keywords: Facility Layout, Systematic Layout Planning (SLP), Graph Method, Production Efficiency, Culture-Based Industry.